Information sources as determinants of use of formal long-term care: a cross-sectional study in Taiwan - Yu-Hung Chang; Chia-Hui Hsu; Yu-Chun Tseng; Wan-Chun Yang; Hung-Yi Chiou (BMC Health Services Research)
Abstract Background An ageing population has heightened the need for long-term care (LTC) access. It is not well understood how information sources, both formal and informal, impact the utilisation of LTC. This study aims to investigate the influence of formal and informal sources on the utilisation of LTC services by Taiwanese families employing migrant live-in caregivers. Methods This study employed a cross-sectional design and used a structured telephone survey to collect data from 441 registered employers from households employing migrant caregivers. This included 216 families using LTC and 225 not using LTC. We collected data on the characteristics of employers and care recipients, as well as LTC-related information sources. Our formal sources (FS) included government promotional events, LTC community site volunteers, healthcare providers, and local LTC management centres, while informal sources (IS) comprised community leaders, friends and relatives, TV, print media, internet, and patient support groups. We assessed perceived information gaps by asking questions about reasons for not using LTC. We used logistic regressions to analyse the associations of FS and IS with LTC use, employer and care recipient characteristics, and perceived information gaps. Results A higher number of FS was positively associated with LTC usage, while an increase in IS was negatively associated. FS and IS were associated with employer socio-demographics such as gender, education level, and care recipient factors, including living arrangements and care needs. FS reduced perceived information gaps, but IS did not. Conclusions Information sources significantly influence the use of LTC among families employing migrant caregivers. Our findings suggest that LTC authorities should implement strategies to enhance the accessibility of formal information sources, while also leveraging informal sources more effectively to support accurate and timely LTC decisions for these families and the wider public.